Implementasi Program Penanganan Banjir Rob Di Wilayah Pesisir Kota Pekalongan - Rizka Febri Ramadhanni; Budi Setiyono; Dzunuwanus Ghulam Manar (Journal of Politic and Government Studies, 2015)
AbstractThe tidal flood if no treatment were significant from the Government of Pekalongan, slums due to tidal flood in the coastal region Pekalongan will be getting bigger and spread to other areas due to sea water every year getting up to the land area would cause tidal flood that came from shoreline. For the Government of Pekalongan set tidal flood management policies as one of the main priorities of development Pekalongan. This study aims to determine the handling policy implementation tidal flooding in coastal areas Pekalongan, obstacles in the implementation of the tidal flood management policies and countermeasures.Based on observations and interviews, the implementation of policies to deal with the tidal flood Coastal Pekalongan by the Public Works Department of the City of Pekalongan is a task as local government agencies Pekalongan in the field of public works, namely the implementation of the development, supervision and maintenance of roads, bridges, irrigation, housing and building area. Based on the four critical variables in the implementation of public policy, the role of the DPU Pekalongan in handling flood Rob Coastal Pekalongan has been running well, namely the smooth communication, availability of resources (resources) enough, the attitude and commitment of the implementers (disposition) strong enough, and the structure of the bureaucracy (bureaucratic strucuture) coordinated. Constraints tidal flood management policy implementation, among others, the border region with other regions of the tidal flood causing tidal flood handling is not complete, there are people who are less concerned rob flood mitigation program, facilities and infrastructure water pump and budget constraints. Efforts are being made to overcome these constraints include coordination with local authorities whose territory borders the tidal flood affected areas, community empowerment in tidal flood management, the improvement of facilities and infrastructure, and increased budget.Keywords: Flood rob, Implementation